Twisting mice move the dystonia field forward - Petersén, Åsa; Kirik, Deniz (The Journal of Clinical Investigation, 2014)
A common form of the hyperkinetic movement disorder dystonia is caused by mutations in the gene TOR1A (located within the DYT1 locus), which encodes the ATPase torsinA. The underlying neurobiological mechanisms that result in dystonia are poorly understood, and progress in the field has been hampered by the absence of a dystonia-like phenotype in animal models with genetic modification of Tor1a. In this issue of the JCI, Liang et al. establish the first animal model with a dystonic motor phenotype and link torsinA hypofunction to the development of early neuropathological changes in distinct sensorimotor regions. The findings of this study will likely play an important role in elucidating the neural substrate for dystonia and should stimulate systematic neuropathological and imaging studies in carriers of TOR1A mutations.